VILLAGE COMMUNITY EMPOWERMENT IN EFFORTS TO IMPROVE FAMILY WELFARE IN PATTAPPA VILLAGE, PUJANANTING DISTRICT, BARRU DISTRICT - A. Pananrangi. M (Sean Institute, 2023)
Village Community Empowerment in Efforts to Improve Family Welfare in Pattappa Village, Pujananting District, Barru Regency The research objective was to find out the efforts to empower village communities in improving family welfare in Pattappa Village. The type of research used qualitative research, and data collection techniques used observation, interviews and documentation. Pujananting District, Barru Regency is quite good, but still not optimal, especially village road infrastructure, utilization of village markets, household businesses, and Kantibmas are quite good.